Facebook revolutions: Transitions in the Arab world, transitions in media coverage? A comparative analysis of CNN and Al Jazeera English's online coverage of the Tunisian and Egyptian revolutions. (20th November 2012) - Bashri, Maha; Netzley, Sara; Greiner, Amy
This study compared how CNN online and Al Jazeera English online covered the uprisings in Tunisia and Egypt through their use of journalistic sources and channels. Sigal's source theory (1973) provided the theoretical framework for the study. A content analysis was conducted examining a total of 941 sources in 70 news stories from the two outlets. Findings show that CNN resorted to the use of American officials and routine channels to report on the uprisings. In comparison, Al Jazeera English mostly used Tunisian and Egyptian citizens as sources as well as enterprise channels. The use of social media by Tunisian and Egyptian activists in the uprisings led the researchers to believe that there would be an extensive use of informal channels in both outlets, but that was not the case. Future studies should examine CNN and Al Jazeera English's coverage of 'neutral events' where no one outlet has a cultural or linguistic advantage.